Leptospiral culture without 5'-fluorouracil revealed improved Leptospira isolation from febrile patients in north-eastern Malaysia - Mohamad Safiee, Amira Wahida; Mohd Ali, Mohammad Ridhuan; Fauzi, Mohd Hashairi; Muhd Besari @ Hashim, Alwi; Chan, Yean Yean; Neela, Vasantha Kumari; Ismail, Nabilah (MDPI, 2020)
Objectives: Isolation of Leptospira by culture represents a definitive growth and confirmation of the disease, yet it is hampered with its nature of slow growth. With slight modification of culture method, the study aims to isolate and characterize Leptospira spp. from patients with acute febrile illness. Methods: A total of 109 blood samples were collected from patients with acute febrile illness that presented at the Emergency Department of Hospital Universiti Sains Malaysia, Malaysia. Clinical samples were subjected to Leptospira IgM Rapid test, microscopic agglutination test (MAT), isolation by culture method, and direct real-time PCR test. For leptospiral isolation, the samples (whole blood and deposit from spun plasma) were cultured into modified Ellinghausen McCullough Johnson Harris (EMJH) media with and without 5’-fluorouracil (5-FU). In every culture positive sample, partial 16S rRNA gene sequencing was performed for molecular identification of the isolates. Phylogenetic analysis was carried out to determine the genetic relatedness among the isolates. An inhibition of 5-FU study was performed on Leptospira interrogans serovar Canicola with different concentrations to compare the growth detection of the tested Leptospira with or without 5-FU within 7 days of incubation. Results: Leptospirosis was diagnosed in 14.7% of patients with acute febrile illness. Two Leptospira spp. (n = 2/109, 1.85%) were successfully isolated from whole blood and deposit from spun plasma samples. B004 and B208 samples were positive at day 11 and day 7, respectively, in EMJH media without addition of 5-FU. Sample B004 was identified as Leptospira interrogans and B208 as Leptospira weilli. Phylogenetic analysis confirmed that both of them were within pathogenic group and they were not related. The 5-FU inhibition study revealed that additional of 5-FU at final concentration of 200 µg/mL to EMJH media demonstrated an inhibitory effect on the growth of the tested strain Conclusion: Isolation of Leptospira spp. using EMJH media without addition of 5’-fluorouracil resulted in a better outcome. Two pathogenic Leptospira isolates were successfully cultivated from patients with acute febrile illness that were genetically not related.